Tourism gentrification in Cape Town’s Bo-Kaap: Socio-economic transformations and displacement - Jessa, Sirhan; Rogerson, Jayne M. (Bulletin of Geography. Socio-economic Series, 2025)
Tourism gentrification is attracting a growing literature in the urban Global North but as yet has received only limited attention in Southern cities. The novel contribution of this paper is to analyse the impact of tourism gentrification on the inner-city heritage precinct of the Bo-Kaap neighbourhood in Cape Town, South Africa. The growth of tourism gentrification is one consequence of the post-apartheid emergence of Cape Town as a leading destination for international tourism. This analysis seeks to understand the effects, the dual processes of tourism and urban redevelopment have on its residents and highlights the challenges facing heritage rich communities in a post-colonial, developing-world context. The results show that whilst tourism presents several opportunities for economic prosperity and cultural preservation, it is not being effectively leveraged for its transformative potential. ...